Influence of Internet use on political participation: gender aspect - Titarenko, Larissa G.; Gao, Jiacheng (Journal of the Belarusian State University. Philosophy and Psychology, 2024)
The impact of Internet use by males and females on their political participation in China is studied. On the basis of comparing the data of the Chinese General Social Survey for 2011 and 2021, the propensity score matching model is constructed. It is found that Internet use has no significant impact on females’ political participation, but reduces the rate of males’ participation in the political life of the country. The results of the study demonstrate the limits of Internet technology use in the process of political participation in China.
Keywords: political participation; Internet use; Chinese General Social Survey; CGSS; Chinа; gender differences; technological optimism